Pengembangan Sistem Prakiraan dan Peringatan Dini Aliran Debris di Kali Putih Kabupaten Jember - Hardjosuwarno, Sutikno (Balai Sabo, 2012)
The frequent landslides triggering the occurrence of debris flow on Putih River had caused victims, so it needs forecasting and warning system. The purpose of this research is to provide debris flow forecasting and war-ning system for Putih River. The forecasting of debris flow was done through a hydrological model, natural dam break model and 2D-debris flow simulation integrated to one CIS based model producing propagation of debris flow and its hazard zone. The result of simulation shows that beginning from elevation 630 m to 280, the propagation velocity were 8.41 mjs and same for the 3 scenarios and decreased to 1.59 mjs at the elevation 318 m due to Significant slope change. Through the comunication system, warning information for debris flow can be disseminated by radio to monitoring stations and relayed to residents by "kentongan" and sirens to allow the residents living in the dangerous zone to escape.